Pemberdayaan Keluarga Sebagai Pengawas Minum Obat (Pmo) Dalam Meningkatkan Kepatuhan Terapi Tuberkulosis Paru Di Rt 02 Rw 14 Kelurahan Sialangmunggu Kecamatan Tuah Madani - Chairil, Chairil; Ningrum, Trisiwi Kusuma; Maswarni, Maswarni (LPPM UMRI, 2026)
Background: Pulmonary tuberculosis remains a major public health problem that requires high adherence to long-term treatment. Low treatment adherence continues to be a major challenge, highlighting the need for family empowerment as Drug Intake Supervisors (DIS). Objective: This community service activity aimed to improve family knowledge and roles as DIS in supporting adherence to pulmonary tuberculosis therapy. Methods: The activity was conducted on May 5, 2026, in RT 02 RW 04, Sialangmunggu Village, Tuah Madani District, involving 35 participants consisting of 23 housewives, 7 fathers, and 5 adolescents. The methods included knowledge assessment using pre-test and post-test, health education, interactive discussions, and family mentoring related to the role of DIS and TB treatment adherence. Results and Discussion: The pre-test results showed an average knowledge score of 56.4, which increased to 82.7 in the post-test. This improvement indicates a significant increase in participants’ understanding of pulmonary tuberculosis, treatment adherence, and the role of the family as DIS. Conclusion: Family empowerment as Drug Intake Supervisors through an educational approach based on pre-test and post-test is effective in improving family knowledge and readiness to support successful tuberculosis therapy. Recommendation: Continuous education and periodic evaluation are recommended to maintain treatment adherence. Keywords: pulmonary tuberculosis,